Simulation of Container Data Processing Using Petri Nets (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article presents a process model for processing container data using Petri nets obtained from an automatic monitoring system for rolling stock and containers. This model makes it possible to check the operation of parallel processes and evaluate the quality of work as a whole.